CRISPR/Cas12a-Assisted Visual Logic-Gate Detection of Pathogenic Microorganisms Based on Water-Soluble DNA-Binding AIEgens - Jiao, Zhe; Yang, Jialing; Long, Xiaojuan; Lu, Yingfang; Guo, Zongning; Peng, Yonglin; Huang, Xuelin; Yin, Yi; Song, Chao; Zhang, Pengfei (Frontiers in Chemistry, 2022)
Here, we developed a rapid, visual and double-checked Logic Gate detection platform for detection of pathogenic microorganisms by aggregation-induced emission luminogens (AIEgens) in combination with Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) /CRISPR associated (Cas). DNA light-up AIEgens (1,1,2,2-tetrakis[4-(2-bromo-ethoxy) phenyl]ethene, TTAPE) was non-emissive but the emission was turned on in the presence of large amount of DNA produced by recombinase polymerase amplification (RPA). When CRISPR/Cas12a was added, all long-stranded DNA were cut leading to the emission quenched. Thus, a method that can directly observe the emission changes with the naked eye has been successfully constructed. The detection is speedy within only 20 min, and has strong specificity to the target. The result can be judged by Logic Gate. Only when the output signal is (1,0), does it represent the presence of pathogenic microorganisms in the test object. Finally, the method was applied to the detect pathogenic microorganisms in environmental water samples, which proved that this method has high selectivity, specificity and applicability for the detection of pathogenic microorganisms in environmental water samples.